Effect of GA3 Application on the Germination of 5-Year Stored Bambara Groundnut (Vigna subterranea (L.) Verdc.) - Anivta, Pricandalu Odillia; Kuswanto, Kuswanto (Department of Agronomy and Horticulture, IPB University, 2026)
Bambara groundnut (Vigna subterranea (L.) Verdc.) is a leguminous crop originating from North Africa, valued for its high protein and carbohydrate content, as well as its ability to adapt to marginal environments. These characteristics make it a promising candidate to support food and nutritional security, particularly in tropical regions. However, its cultivation and seed quality management remain limited, requiring strategies to improve germination and seedling establishment. Gibberellic acid (GA3) is a plant growth regulator widely known to stimulate seed germination and enhance vigor. This study aimed to assess the effect of GA3 on the germination performance of Bambara groundnut seeds stored for five years. Three genotypes (SS 3.4.2, BBL 1.1, and TVSU 8.6) were treated with GA3 at concentrations of 0, 75, 150, and 225 ppm, and germination and vigor parameters were evaluated. The results showed that GA3 application improved the performance of aged seeds, with 225 ppm identified as the most effective dose. Genotype SS 3.4.2 responded particularly well at this concentration, while BBL 1.1 consistently exhibited superior overall performance across treatments. These findings highlight the potential of GA3 to mitigate the adverse effects of seed aging and enhance seedling establishment. The application of GA3 represents a practical approach for improving the viability of stored seeds.